Cementless versus Cemented Total Knee Arthroplasty Using the Same Implant Design: A Mean 5-Year Follow-up Study - Miller, Adam J.; Nadar, Arun C.; Granade, Charles M.; Smith, Langan S.; Yakkanti, Madhusudhan R.; Malkani, Arthur L. (The Journal of Knee Surgery, 2024)
Cementless implant use continues to increase primarily due to increased numbers of younger and obese patients opting for primary total knee arthroplasty (TKA). Given the increased use of cementless implants, the purpose of this study was to evaluate the midterm clinical performance of cementless TKA using a highly porous tibial baseplate compared with its cemented counterpart of the same system. We conducted a retrospective case-control study of 400 patients undergoing primary TKA that included 200 patients with cementless components matched for age and body mass index (BMI) to 200 patients with cemented implants of the same implant design with a 5-year follow-up. We evaluated clinical results, complications, revisions, and overall survivorship between the cohorts. Statistical analysis was performed using student t-test and chi-square analysis. There was no statistical difference in age (64.3 vs. 64.3 p = 0.81), BMI (34 vs. 33.1 p = 0.19), preoperative Knee Society Score (KSS) function (41 vs. 32.3 p = 0.22), and preoperative KSS knee score (39.2 vs. 38.3 p = 0.54) between the cementless and cemented cohorts, respectively. The cementless group had seven revisions, while the cemented group had nine revisions (p = 0.609). The cementless group had one revision due to aseptic loosening versus five in the cemented group (p = 0.09). Postoperative 5-year KSS knee scores were 92.84 versus 91.75 (p = 0.386) and function scores were 81.81 versus 69.65 (p = 0.00004) in the cementless and cemented groups, respectively. The cementless group had survivorship of 96.5% for all-cause revision compared with 95.5% in the cemented group at 5-year follow-up (p = 0.60). Cementless TKA using a highly porous tibial baseplate showed excellent midterm results with one case of aseptic loosening at 5-year follow-up and with similar Knee Society outcome scores and survivorship compared with the cemented group. Cementless TKA demonstrated noninferiority to cemented TKA and could be used as an alternative mode of fixation in patients opting for primary TKA. Additional long-term follow-up is needed to determine if cementless TKA can demonstrate improved survivorship over cemented TKA.
Keywords: primary total knee arthroplasty; cementless TKA; cemented TKA; outcomes; complications; aseptic loosening